EVALUATION OF ARISTOLOCHIA BRACTEOLATA LINN. FOR ANTIMICROBIAL ACTIVITY, Î±-GLUCOSIDASE INHIBITION, AND ITS PHYTOCHEMICAL CONSTITUENTS - Das, Trayee Sarkar; R, Latha; P, Agastian (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To evaluate antimicrobial efficacy, Î±-glucosidase inhibition and various phytochemical constituents of Aristolochia bracteolata Linn. Methods: Soxhlet extraction by using hexane, ethyl acetate and methanol solvents, antimicrobial, Î±-glucosidase inhibition assay, qualitative and quantitative phytochemical estimation. Results: The results revealed that the methanolic extract showed significant antibacterial and antifungal activity. The maximum zone of inhibition was against Bacillus subtilis (24 mm), Yersinia enterocholitica (22 mm) and Proteus vulgaris (20 mm) at the concentration of 5 mg/ml of extract. Methanolic extract showed MIC value of 250 Î¼g/ml against all the fungal pathogens. The methanol extract showed 78.27% of Î±-glucosidase inhibition. The phytochemical tests showed the presence of phenols, terpenoids, tannins, flavonoids, glycosides, carbohydrates in methanol extract. Total phenolic and total flavonoid content of methanol extract were 103.21Â±1.23 mg catechol equivalents/100 g extract and 53.01Â±1.78 mg quercetin equivalents/100 g respectively. Conclusion: The results conclude that the extracts of Aristolochia bracteolata exert multiple biological properties due to the presence of flavonoids and phenols. It is also an effective glucosidase inhibitor. It can be used to obtain novel antibacterial compounds for the treatment of infectious diseases in future. Key words: Aristolochia bracteolata Linn, Phytochemical, Phenolic and flavonoid content, antimicrobial activity, Î±-glucosidase inhibition. Â